2017
DOI: 10.4236/jss.2017.512007
|View full text |Cite
|
Sign up to set email alerts
|

Immigrant Status and Its Impact on Access to Health Care

Abstract: This paper explores disparities in health care access for undocumented immigrants in the United States. Using the case of California, we find that less than half of undocumented immigrants in this state report having health insurance. Additionally, our estimates show that, among the insured, US-born and naturalized citizens are significantly more likely to have a doctor visit in the previous year when compared to undocumented immigrants (aOR = 1.53%; 95% CI 1.15 -2.04, aOR = 1.40%; 95% CI 1.05 -1.87, respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 16 publications
2
3
0
Order By: Relevance
“…Our findings using the statistical matching approach are largely consistent with results from studies with geographically limited samples (Goldman, Smith, and Sood 2005;Navarro, Ibarra, and Anglemyer 2017;Ortega et al 2018) and work using the restricted SIPP (Ro and Van Hook 2021). While our analysis revealed that 21% of naturalized citizens, 45% of LPRs, and 66% of unauthorized immigrants were uninsured, Goldman, Smith, and Sood (2005) found that 23% of naturalized citizens, 38% of permanent residents, and 68% of unauthorized immigrant adults in Los Angeles were uninsured.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…Our findings using the statistical matching approach are largely consistent with results from studies with geographically limited samples (Goldman, Smith, and Sood 2005;Navarro, Ibarra, and Anglemyer 2017;Ortega et al 2018) and work using the restricted SIPP (Ro and Van Hook 2021). While our analysis revealed that 21% of naturalized citizens, 45% of LPRs, and 66% of unauthorized immigrants were uninsured, Goldman, Smith, and Sood (2005) found that 23% of naturalized citizens, 38% of permanent residents, and 68% of unauthorized immigrant adults in Los Angeles were uninsured.…”
Section: Discussionsupporting
confidence: 86%
“…While our analysis revealed that 21% of naturalized citizens, 45% of LPRs, and 66% of unauthorized immigrants were uninsured, Goldman, Smith, and Sood (2005) found that 23% of naturalized citizens, 38% of permanent residents, and 68% of unauthorized immigrant adults in Los Angeles were uninsured. In California, 52% of the unauthorized were uninsured, compared to 14% and 16% of US-born citizens and naturalized citizens, respectively (Navarro, Ibarra, and Anglemyer 2017). Among Hispanics, we find that 32% of naturalized citizens, 60% of LPRs, and 74% of unauthorized immigrants lack insurance coverage, similar to estimates made by Ro and Van Hook (2021) using restricted SIPP; they show that 31% of naturalized, 58% of LPR, and 77% of unauthorized immigrant Hispanic adults were uninsured.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations